Functional characteristics of bone marrow stromal cells in patients with acute leukemia - I. M. Barhatov; N. Y. Tsvetkov; A. I. Shakirova; D. S. Romanyuk; O. G. Smykova; L. S. Zubarovskaya; B. V. Afanasyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
Pathogenesis of acute leukemia is associated with the presence of genetic and functional aberrations in hematopoietic stem cells. However, as one of the possible factors contributing to the progression of disease could be regarded as the pull of the stromal cells of bone marrow. In this paper we evaluated the major functional characteristics of stromal cells: proliferative activity, hematopoiesis supportive and differentiation ability, as well as analysis of the expression of adhesion molecules. Stromal cells derived from acute leukemia patients in comparison with healthy donors are characterized by a high proliferative activity and a pronounced ability to osteogenic and adipogenic differentiation with prominent expression of hematopoietic stem cells homing mediating molecules.